2012
DOI: 10.1371/journal.pone.0049879
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GluA2 AMPA Receptor Subunits Reduces the Dendritic Arborization of Developing Spinal Motoneurons

Abstract: AMPA receptors lacking the GluA2 subunit allow a significant influx of Ca2+ ions. Although Ca2+-permeable AMPA receptors are a familiar feature at early stages of development, the functional significance of these receptors during the maturation of the nervous system remains to be established. Chicken lumbar motoneurons express Ca2+-permeable AMPA receptors at E6 but the Ca2+ permeability of AMPA receptors decreases ∼3-fold by E11. Considering that activity-dependent changes in intracellular Ca2+ regulates dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…has reported that GluA2 subunits are expressed and organized in axonal growth cones of neurons 24 . Overexpressing GluA2 has also been shown to increase dendritic length, arborization and spine density of pyramidal neurons 28 29 30 , while downregulation results in a reduction of dendritic arborization in early spinal motoneurons 34 . A recent study also provided evidence for the localization of GAPDH with GluA2 and L1 at lens fibre cell membranes, further illustrating the potential involvement of this complex in axon formation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…has reported that GluA2 subunits are expressed and organized in axonal growth cones of neurons 24 . Overexpressing GluA2 has also been shown to increase dendritic length, arborization and spine density of pyramidal neurons 28 29 30 , while downregulation results in a reduction of dendritic arborization in early spinal motoneurons 34 . A recent study also provided evidence for the localization of GAPDH with GluA2 and L1 at lens fibre cell membranes, further illustrating the potential involvement of this complex in axon formation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies suggested that the global transcriptional dysregulation of ionotropic glutamate receptor subunits alone does not account for the selective vulnerability of neurons and may, instead, be involved in the reorganization of the injured spinal cord . This notion may explain why NR2D mRNA in dormant FMNs was not elevated to resist neurodegeneration, as suggested by a study regarding protective pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, of all remodeling activities, synaptic connection elimination and rearrangement around FMNs take place concomitantly to orchestrate dynamic structural changes . One study showed that, in mammalians, the downregulated glutamate receptor expression by short‐interfering RNA against specific regions of the GluR2 transcript significantly reduced the dendritic arborization of motoneurons, but motoneuron survival and network activity were not affected . In another study, the knockdown or overexpression of GluA1 (GluR1) modulated the dendrite elaboration on spinal motor neurons during the developmental phase .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides their function in synaptic transmission, neurotransmitter receptors also have functions in synaptogenesis and neuronal wiring. In chicken, the GluA2 subunit of AMPA receptors is required for the formation of dendritic arborizations (Yoon et al, 2012 ), and in mammalian brains, it can modulate spine formation (Saglietti et al, 2007 ; Lee et al, 2016 ). The murine GABA A receptor can induce synaptogenesis (Oh et al, 2016 ), and it is also required for spine formation (Heinen et al, 2003 ).…”
Section: Roles Of Rna Metabolism In Neuronal Wiring and Remodelingmentioning
confidence: 99%